Prediction of bioactive compounds of Cabe Jamu (Piper retrofractum) Sebagai Senyawa as Anti Diabetic Agent - Cahyo Indarto; Supriyanto Supriyanto (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Diabetes mellitus is a metabolic disorder disease which is the fourth leading cause of death in Indonesia. The number of people with diabetes in Indonesia shows an increase from year to year, in 2007 people with diabetes reached 14.7% of the population and it is predicted that in 2030 the number of people with diabetes in Indonesia will reach 21.3 million people. Globally, Indonesia ranks fourth in the number of diabetics after India, China and the United States. Herbal medicines from spices have the opportunity to be developed into antidiabetic agents, with considerations of safety, minimal side effects and cheap. Several types of spices have been reported to be used as antidiabetic agents. Cabe jamu, one of the famous spices in Madura, has been reported to have many health benefits. This study will identify the active compounds in cabe jamu that have the ability as antidiabetics by using a molecular docking approach. The results of the study found that cabe jamu has 22 active compounds that have the potential as herbal medicines. Of the 22 active compounds, 10 of them were successfully docked with diabetes aldose reductase protein. The results of this study indicate that the active compounds contained in cabe jamu have the ability as an antidiabetic agent. Based on the strength of the hidrogen bond, and the absence of toxic potential, 3 active compounds from cabe jamu that have strong antidiabetic abilities and no toxic potential were obtained, namely piperine, retrofractamide C, and guineensine.